(untitled) - Zorbas, Dino (United States of America, 2014)
Suitable for a single semester undergraduate course on electromechanical energy conversion devices or electric machines, this title strikes a balance between theoretical coverage, easy explanations, and practical applications, presenting real world applications of concepts without compromising on the rigor or the continuity of the text
Keywords: Electric machinery,Máy móc thiết bị điện